PLAY AND SPEAKING ANXIETY TOWARDS ENGLISH SPEAKING SKILL - Eppendi, Jhoni (Borneo Journal of English Language Education, 2020)
The purposes of this study were to find out whether or not (1) there was a significant difference in English speaking achievement between the students who were taught by using role-play technique and those who were not, (2) there was a significant interaction effect of role-playing and speaking anxiety on English speaking achievement, and (3) there was a considerable difference in speaking performance between the students who have high and low levels of speaking anxiety. 57 out of 80 tenth graders of hotel accommodation of SMKN 3 Palembang were selected randomly as the sample. The ‘Foreign Language Classroom Anxiety Scale’ and an oral test were used to collect the data. The intervention was conducted for sixteen meetings, two teaching hours in each. The findings showed the main difference between both groups was 4.6, which the experimental led the control group. Also, the two-ways ANOVA indicated that there was a significant interaction between role-playing and speaking anxiety on students’ speaking achievement. The main difference score between low and high levels of speaking anxiety was 3.68, in which low-level speaking anxiety drove the upper level. It is clear that speaking anxiety plays an essential role in students’ speaking performance